Skogssådd med tall och gran : effekter av fröegenskaper och skärm/hygge på plantbildning, överlevnad och tillväxt de två första åren efter sådd - Larsson, Niclas (SLU/Dept. of Silviculture, 2006)
Over the past few years the Swedish forestry industry has become increasing interested in direct seeding. Although, in practice, this interest has been restricted to pine seed, the knowledge and techniques that have been developed for pine seeding can readily be transferred to spruce. Direct seeding is a method that is of interest to the forestry industry since it can lead to lower regeneration costs, denser stands and better root development than the more conventional planting method. This study evaluated experiments that focused on direct seeding of spruce in the northern Sweden. Skogforsk set-up the experiments in Gideå and Sävar in 2003. They were inventoried in the spring and autumn of 2004. The collected data were compiled and comparisons of seedling emergence, survival and seedling height were made between: - Direct seeding on clear-cut and in shelterwood. - Different seed lots of pine and spruce. The results showed that: • Direct seeding of spruce can be as functional as pine seeding, in both shelterwood and on clear-cuts, during the first two years after the seeding. • Seedling emergence after one growing season was significantly highest on the clear-cut in Gideå for both tree species. In Sävar, seedling emergence was significantly higher in the shelterwood. • The survival rate of the seedlings was almost the same in shelterwood and the clear-cut areas with the exception of between the autumn 2003 and the spring 2004 when the survival rate was significantly higher in the shelterwood in Sävar. • Germination capacity, germination energy or seed weight did not have a significant association with the survival of the seedlings. • The mean height of the seedlings was significantly higher on the clear-cut than in the shelterwood in Gideå. No such difference was found in Sävar. • The survival rate was significantly higher for pine than spruce between the autumn 2003 and the spring 2004 in the shelterwood in Sävar (all seed lots). There was no such difference for the survival rates between the spring and the ...